2016
DOI: 10.1371/journal.pone.0149566
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Fitness to Drive in Patients with Alzheimer's Dementia

Abstract: The number of patients with Alzheimer’s disease (AD) is increasing and so is the number of patients driving a car. To enable patients to retain their mobility while at the same time not endangering public safety, each patient should be assessed for fitness to drive. The aim of this study is to develop a method to assess fitness to drive in a clinical setting, using three types of assessments, i.e. clinical interviews, neuropsychological assessment and driving simulator rides. The goals are (1) to determine for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
106
0
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(123 citation statements)
references
References 64 publications
5
106
0
12
Order By: Relevance
“…Indeed, currently there is no consensus in the literature about the role of driving simulators in predicting an individual's fitness to drive, although studies have shown significant correlations between reaction time measures and on-road driving performance. 34-38 Thus, considering prior evidence and the fact that off-road tests (including driving reaction time assessment) are primarily to complement on-road tests and not to replace them; we believe that performing an on-road test is beyond the scope of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, currently there is no consensus in the literature about the role of driving simulators in predicting an individual's fitness to drive, although studies have shown significant correlations between reaction time measures and on-road driving performance. 34-38 Thus, considering prior evidence and the fact that off-road tests (including driving reaction time assessment) are primarily to complement on-road tests and not to replace them; we believe that performing an on-road test is beyond the scope of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…AD patients also tended to drive slower [64, 78, 80], took longer to complete the driving tests [78, 79], had less brake pressure [78], and made more judgmental errors (e.g., accidents, collisions) [80]. They failed to stop at traffic lights [80, 81] and exceeded the speed limit more often than controls [81].…”
Section: Resultsmentioning
confidence: 99%
“…This decrease in functional abilities can lead to an overall loss of fitness to drive and an increased crash risk (Marshall, 2008). Since decline of functional abilities often occurs with disease, it is not surprising that fitness to drive studies have often focused on elderly with diagnosed diseases such as Alzheimer's or Parkinson's Disease (Carr, Barco, Wallendorf, Snellgrove, & Ott, 2011Snellgrove, & Ott, 2011Grace et al, 2005;Piersma et al, 2016).…”
Section: Introductionmentioning
confidence: 99%